Optimization of experimental conditions of microbial desulfurization in coal mine using response surface methodology - Ai, Chun‐ming; Sun, Ping‐ping; Zhao, Dan; Mu, Xiao‐zhi (Frontiers in Bioengineering and Biotechnology, 2022)
To reduce the risk of spontaneous combustion during coal storage and transportation, microbial desulfurization technology is used to reduce the content of inorganic sulfur in coal. A strain of Aciditithiobacillus ferrooxidans was purified from coal mine water in Datong, Shanxi Province, and its desulfurization test conditions were optimized. Taking the inorganic sulfur removal rate of coal as the response value. The Plackett-Burman design method was used to screen the main factors affecting the response value. And the response surface method was used to establish the continuous variable surface model to determine the interaction between the factors. The results show that the three main factors affecting the response value and their significance order are temperature > coal particle size > desulfurization time, and the interaction between temperature and coal particle size has the greatest effect. When the temperature is 29.50℃, the coal size is 100 mesh, and the desulfurization time is 11.67 days, the desulfurization effect is the best, and the removal rate of inorganic sulfur can reach 79.78%, which is close to the predicted value, and the regression effect is wonderful.